2014
DOI: 10.1002/ajim.22331
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness, oxidative stress, and smoke exposure in wildland firefighters

Abstract: Objectives To assess the association between exposure, oxidative stress, symptoms, and cardiorespiratory function in wildland firefighters. Methods We studied two Interagency Hotshot Crews with questionnaires, pulse wave analysis for arterial stiffness, spirometry, urinary 8-iso-prostaglandin F2α (8-isoprostane) and 8-hydroxy-2′-deoxyguanosine (8-OHdG), and the smoke exposure marker (urinary levoglucosan). Arterial stiffness was assessed by examining levels of the aortic augmentation index, expressed as a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 47 publications
1
35
2
6
Order By: Relevance
“…In one study, urinary levoglucosan, a biomarker of wood smoke exposure, was associated with higher oxidative stress scores. These, in turn, were linked to stiffer arteries in WLFFs [Gaughan et al, ]. Of note in our survey, two subclinical and well‐established risk factors for cardiovascular events, high blood pressure, and heart arrhythmia, were associated significantly with a longer history of employment as a WLFF.…”
Section: Discussionsupporting
confidence: 49%
“…In one study, urinary levoglucosan, a biomarker of wood smoke exposure, was associated with higher oxidative stress scores. These, in turn, were linked to stiffer arteries in WLFFs [Gaughan et al, ]. Of note in our survey, two subclinical and well‐established risk factors for cardiovascular events, high blood pressure, and heart arrhythmia, were associated significantly with a longer history of employment as a WLFF.…”
Section: Discussionsupporting
confidence: 49%
“…40 Collectively, these studies suggest that particulate exposure, including wood smoke, increase 8-isoprostane concentrations in body tissues including urine. The results in our study also suggest that 8-isoprostane levels in EBC are affected by wood smoke inhalation during physical activity that mimics wildland firefighting.…”
Section: Discussionmentioning
confidence: 96%
“…The serum findings are in contrast with human experimental wood smoke exposure studies showing either no change or a decrease in serum IL-6, which may have to do with the extreme nature of the exposure in the Swiston study or the different chemical compositions of wildfire smoke and wood smoke (Ghio et al, 2012; Stockfelt et al, 2012). A recent study by Gaughan et al showed an increase in two urinary markers of oxidative stress, 8-isoprostane and 8-oxo-2′-deoxyguanosine (Gaughan et al, 2014). This is consistent with one study of relatively high human exposure to wood smoke showing increased urinary 8-iso-prostaglandinF2α, while another study with lower concentration smoke exposure found decreased urinary 8-iso-prostaglandinF2α (Barregard et al, 2006; Stockfelt et al, 2013).…”
Section: Health Effects Of Wildfire Smokementioning
confidence: 99%